KRITIK NALAR ISLAM M. ARKOUN - Farid, Mohamad (Jurnal Kajian Hukum Islam, 2019)
Naskah ini mengakaji tentang pemikiran M. Arkoun yang mana sederet karya yang bersangkutan dapat di lihat diantaranya adalah; (1) The Unthought in Contemporary Islamic; (2) Thought, 2002, London; (3) The Aga Khan Award as a Process of Thinking, 1998; (4) L'immigration: défis et richesses, LXXIIe session des Semaines sociales de France, Paris and Issy-les-Moulineaux, France, 1997; (5) Spirituality in Architecture, 1995; (6) Rethinking Islam: common questions, uncommon answers, Boulder, Col. 1994; (7) Les cultures del Magreb, 1994; (8) L'Islam et les musulmans dans le monde, 1993; (9) La passione del conoscere Preta, Lorena, 1993; (10) Architectural Alternatives in Deteriorating Societies, 1992; (11) The Meaning of Cultural Conservation in Muslim Societies, 1990; (12) A Policy for Architectural Conservation, 1990; (13) Muslim Character: The Essential and the Changeable, 1989; (14) Current Islam Faces its Tradition, 1989 (15) L'islam, morale et politique, 1986; (16) Pour une critique de la raison islamique, 1984; (17) Islam, Urbanism, and Human Existence Today, 1983; (18) Building and Meaning in the Islamic World, 1983 )19) L'Islam, religion et société, 1982; (20) Lectures du Coran, 1982; (21) La Pensée arabe, 1975; (22) Essais sur la pensée islamique, 1973; (23) Les Musulmans. Consultation islamo-chrétienne entre Muhammad Arkoun [et al.] et Youakim Moubarac. Postface par M. Kamel Hussein et par Daniel Pézeril, 1971; (24) Contribution à l'étude de l'humanisme arabe au 4e/10e siècle, 1969/1970